Influence of ferroelectricity on the photoelectric effect of LiNbO3. - Dunn, Steve; Tiwari, Divya (American Institute of Physics (AIP), 2008)
A comparison between the influence of domain dependent photochemical and photoelectric cation reduction on the surface of LiNbO3 is presented. The reduction of the photoelectric threshold for LiNbO3 due to the polar nature of the crystal allows high energy UV irradiation to produce free electrons that can participate in photochemical reduction of silver nitrate on the surface. This is in addition to the previously understood phenomenon of domain directed photophysics, where influences on space charge layer due to the internal dipole of a ferroelectric determine the carrier at the surface. We show that the interaction of photoelectric and domain dependent influences can be observed in LiNbO3 due to the low electron affinity (ca 2eV) and large band bending (0.8eV).